Kombinasi Bridging dan Kegel Exercise Untuk Menurunkan Inkontinensia Urine Pada Lansia - Faisal, T. Iskandar; Khaira, Nuswatul; Veri, Nora (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Urinary incontinence is a person's inability to hold out urine and if it is not handled properly it will lead to complications, namely urinary tract infections, infections of the skin, especially the pubic area, disturbed sleep patterns, pressure sores, and redness. Kegel and Bridging exercises are exercises to strengthen the pelvic muscles for the treatment of urinary incontinence. The aim of the study was to determine the effect of a combination of Bridging exercise and Kegel Exercise on urinary incontinence. Quasy experimental research design with pretest posttest control group design. The elderly were divided into four groups, namely the control group, the bridging exercise treatment, the Kegel exercise group, the combination bridging group and the Kegel exercise group with a total sample of 24 elderly people. Research Results Bridging exercise, Kegel exercise and a combination of bridging and Kegel exercise were able to reduce urinary incontinence scores, however, the combination Bridging exercise was the fastest treatment in reducing urinary incontinence scores in the elderly compared to bridging and Kegel exercises which were carried out separately.